Analysis of human resources for oral health globally: inequitable distribution. (3rd January 2018) - Gallagher, Jennifer E.; Hutchinson, Lynn
Abstract : Background: Oral diseases affect most of the global population. The aim of this paper was to provide a contemporary analysis of 'human resources for oral health' (HROH) by examining the size and distribution of the dental workforce according to World Health Organization (WHO) region and in the most populous countries. Method: Publically available data on HROH and population size were sourced from the WHO, Central Intelligence Agency, United Nations, World Bank and the UK registration body. Population‐to‐dentist and dental‐workforce ratios were calculated according to WHO region and for the 25 most populous countries globally. Workforce trends over time were examined for one high‐income country, the UK. Results: The majority of the world's 1.6 million dentists are based in Europe and the Americas, such that 69% of the world's dentists serve 27% of the global population. Africa has only 1% of the global workforce and thus there are marked inequalities in access to dental personnel, as demonstrated by population to dental‐workforce ratios. Gaps exist in dental‐workforce data, most notably relating to mid‐level clinical providers, such as dental hygienists and therapists, and HROH data are not regularly updated. Workforce expansion and migration may result in rapid changes in dentist numbers. Conclusion: Marked inequalities in the distribution of global HROH exist between regions and countries, with inequalities most apparent in areas of high population growth. Detailed contemporary data on all groups of HROH are required to inform global workforce reform in support of addressing population oral health needs.